The Weaknesses in Handling Fraud in The Capital Market Practices - Suhanan, Aan; Gunarto, Gunarto; Mashdurohatun, Anis (Law Development Journal, 2023)
The weaknesses of the legal substance relating to the handling of fraud in the Capital Market practices are fundamentally contained in the substance of Law Number 8 of 1995 on Capital Market ("UUPM"). Law enforcement has actually become one of the focuses of attention from law enforcers, such as in the case of state losses incurred due to fraudulent acts in the capital market committed by Perusahaan Gas Negara (PGN) is included in the criminal act of corruption because it indicates the elements of corruption. Officials at State-Owned Enterprises (SOEs) who commit fraud in accordance with the provisions can be categorized as corruption. Corrupt practices in the financial markets that cost the state large amounts of money have not gone unnoticed. Internationally, there is currently an effort to mainstream the financial sector into the jurisdiction of anti-corruption laws. This study concerns on the weaknesses of substance, structure, and legal culture regarding the handling of fraud in the Capital Market practices which is still lacking to overcome fraud related to the practices of Insider Trading.